Neuro-industrial engineering: the new stage of modern IE – from the human-oriented perspective. (15th January 2013) - Ma, Qingguo; Ji, Wenjing; Fu, Huijian; Bian, Jun
This paper reviewed the three stages of the evolvement of Industrial Engineering from the human-oriented perspective and analysed the new problems faced by existing theories in modern production process. According to the idea and the methodology of Neuro-Industrial Engineering (Neuro-IE), this paper gave a more detailed account of the applied branches of Neuro-IE based on the combination of the neurophysiologic information from brain's reaction to the production environment and process, which is a brand-new perspective in both Services Operation and Informatics. Meanwhile, the differences between traditional IE and Neuro-IE, between Neuroergonomics and Neuro-IE were discussed in somewhat detail. The basic hypotheses underlying traditional IE and Neuro-IE, i.e. the cornerstones of them, were also compared.